1998
DOI: 10.1115/1.2834412
|View full text |Cite
|
Sign up to set email alerts
|

A Thermohydrodynamic Lubrication Analysis to Design Large Two-Pad Journal Bearing With Cooling Ditches

Abstract: A newly developed large two-pad journal bearing with cooling ditches and viscous pump for turbines of electric utilities was analyzed theoretically. The turbulent thermohydrodynamic lubrication analysis was done in connection with the flow analysis of oil circulating system through the cooling ditches and the viscous pump. The complicated simultaneous equations concerned with the oil flow in the bearing were solved and used to design a bearing of 535 mm diameter which will make its appearance in a near future.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Taniguchi et al [4] applied their turbulent THD model to a newly designed large two-pad tilting-pad journal bearing with cooling ditches on the back surface of the pads. They found that the predicted bearing performance was in good agreement with measurements obtained in a full-size bearing test rig.…”
Section: Turbulent Thd Modelmentioning
confidence: 99%
“…Taniguchi et al [4] applied their turbulent THD model to a newly designed large two-pad tilting-pad journal bearing with cooling ditches on the back surface of the pads. They found that the predicted bearing performance was in good agreement with measurements obtained in a full-size bearing test rig.…”
Section: Turbulent Thd Modelmentioning
confidence: 99%
“…14 An additional key point might be a reduction of pads, and experimental and analytical results of two pad bearing were reported. 15…”
Section: Introductionmentioning
confidence: 99%